Achieving emissions reductions for environmental justice communities through climate change mitigation policy - Sheats, Nicky, author (Colorado State University. Libraries, 2017)
This paper focuses on emissions reductions for EJ communities under the Clean Power Plan in particular as well as climate change mitigation policy in general and argues that these reductions should be both mandatory and planned. The next section of the paper discusses why, from an EJ perspective, equity should be an integral part of climate change mitigation policy; then the need for climate change mitigation policy to produce emissions reductions for EJ communities is discussed; this is followed by an explanation of why neither the Clean Power Plan nor carbon trading programs in general can guarantee emissions reductions for EJ communities in the manner needed; then a specific mechanism for achieving these reductions under the Clean Power Plan is proposed; and the paper concludes with several final thoughts. Many of the ideas contained in this paper have been presented before in various forms in comments submitted by this author on behalf of the New Jersey Environmental Justice Alliance. However, additional ideas, discussion and detail are included here.
Presented at the Environmental justice in the Anthropocene symposium held on April 24-25, 2017 at the Lory Student Center, Colorado State University, Fort Collins Colorado. This symposium aims to bring together academics (faculty and graduate students), independent researchers, community and movement activists, and regulatory and policy practitioners from across disciplines, research areas, perspectives, and different countries. Our overarching goal is to build on several decades of EJ research and practice to address the seemingly intractable environmental and ecological problems of this unfolding era. How can we explore EJ amongst humans and between nature and humans, within and across generations, in an age when humans dominate the landscape? How can we better understand collective human dominance without obscuring continuing power differentials and inequities within and between human societies? What institutional and governance innovations can we adopt to address existing challenges and to promote just transitions and futures?
Keywords: equity; climate change mitigation policy; emissions reductions